2013
DOI: 10.4028/www.scientific.net/amm.295-298.3228
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influencing Factors of Coal Fines Produced by CBM Wells in Hancheng Block, Shaanxi Province, China

Abstract: To ensure the continuous and stable exhaust process of coalbed methane wells, prevent coal fines from lowering the guidance ability of seepage channel, and solve the problem of stuck pump and submerged pump caused by gathering of coal fines, taking Hancheng block as the experimental area, this paper analyses on the source of the coal fines, and divides it into two categories of original coal fines and secondary coal fines. Based on the characteristics of coal petrography, coal structure, coal seam and engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Zhang et al developed reasonable measures to control coal fine production by analyzing the mechanism of coal fine production . Zhu et al provided guidance on coal fine control measures by dividing coal fine types and production factors . Li et al mixed calcium sulfoaluminate particles with sand to create a new fracturing proppant that improves the efficiency of CBM extraction by reducing coal fine generation and preventing coal fine migration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al developed reasonable measures to control coal fine production by analyzing the mechanism of coal fine production . Zhu et al provided guidance on coal fine control measures by dividing coal fine types and production factors . Li et al mixed calcium sulfoaluminate particles with sand to create a new fracturing proppant that improves the efficiency of CBM extraction by reducing coal fine generation and preventing coal fine migration .…”
Section: Introductionmentioning
confidence: 99%
“…15 Zhu et al provided guidance on coal fine control measures by dividing coal fine types and production factors. 18 Li et al mixed calcium sulfoaluminate particles with sand to create a new fracturing proppant that improves the efficiency of CBM extraction by reducing coal fine generation and preventing coal fine migration. 19 Shi et al found that NaHCO 3 may fix a portion of coal fines at its source through coagulation and promote the movement of another portion of fine particles by reducing the viscosity, 20 thus reducing the negative impact caused by coal fines.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of coal fines production has long been severely affecting the stable production of coalbed methane. During the generation and migration process, coal fines can block coal reservoir fractures, causing a decrease in reservoir permeability and blocking the bottom-hole screen pipes and pump inlets, leading to production failures. The production of coal fines during the coalbed methane production process is controlled by engineering and geological factors, with different production stages exhibiting varying coal fines production patterns. The drilling process, including the grinding of coal seams by drilling tools, the erosion of coal reservoirs by water flow during drainage, and the abrasion of coal reservoirs by fracturing fluids or proppants during fracturing, can result in a large amount of coal fines. In addition, stress changes induced by coalbed methane production can also lead to shear failure in the coal reservoir, resulting in the generation of coal fines . Geological structures and coal quality also affect the production of coal fines; , tectonic coal, which forms under tectonic deformation, has a complex pore structure and features low strength and low permeability, making it prone to damage and the production of large amounts of coal fines during the production process and causing reservoir damage and seriously affect production.…”
Section: Introductionmentioning
confidence: 99%
“… 12 15 In addition, stress changes induced by coalbed methane production can also lead to shear failure in the coal reservoir, resulting in the generation of coal fines. 16 Geological structures and coal quality also affect the production of coal fines; 5 , 6 tectonic coal, which forms under tectonic deformation, has a complex pore structure and features low strength and low permeability, making it prone to damage and the production of large amounts of coal fines during the production process 17 − 20 and causing reservoir damage and seriously affect production.…”
Section: Introductionmentioning
confidence: 99%
“…If the fallen coal fine can be properly discharged, the seepage channel can be expanded, the permeability can be improved, and the gas production of a single well can be increased. On the other hand, when the detached coal fines are too large or the hydrodynamic conditions are insufficient to transport them, the precipitated coal fine will block the pores and fractures of the coal reservoir, leading to a decrease in permeability [6,7]. The impact of a large amount of coal fine production on the CBM drainage mainly includes the following aspects [8]: (1) reduced permeability, difficulty in drainage and pressure reduction, and difficulty in gas desorption; (2) coal fine can cause wear on the pump barrel and plunger, causing problems such as buried pipe columns and pump jamming due to the accumulation of coal fine; and (3) the mixture of coal fine increases the fluid concentration and the construction pressure.…”
Section: Introductionmentioning
confidence: 99%